A pilot study of the influence of an inclination on V2 skate technique in cross-country skiing - Sugimoto, T.; Yamamoto, K.; Kawahatsu, K. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: In a cross-country (CC) skiing competition, a V2 skate technique (V2) has in recent years become more widely applied on uphill terrain, where V1 skate technique typically was used with the appearance of the sprint race. Skiers perform one double pole stroke on each leg push-off in a V2. The purpose of this study was to examine the influence of an inclination on a V2 motion.